A residência multiprofissional em saúde como espaço formativo e interdisciplinar: a experiência do serviço social em um hospital universitário público - Rolim, Gerusa do Nascimento (2015)
The Health Multidisciplinary Residence, a training proposal, constitutes significant space that seeks the transformation of practices, guided by the reflection of the reality and the principles of the Sistema Único de Saúde - SUS (Unified Health System, Brazil‟s publicly funded health care system). The Residence contributes to resize the daily life of health services and the work of social worker, articulating practice and theoretical fields, anchored in the Diretrizes Curriculares da Associação Brasileira de Ensino e Pesquisa em Serviço Social (Curriculum Guidelines of the Brazilian Association of Education and Research in Social Work) and in the Ethical-Political Project of the profession. Thus, this study aims at understanding the contributions of a program named Residência Integrada Multiprofissional em Atenção Hospitalar à Saúde - Resmult (Multidisciplinary Integrated Residence in Hospital Health Care) of the Universidade Federal do Ceará - UFC, in the Transplant Assistance field as a space for training social workers in an interdisciplinary perspective. This is a case study using the qualitative approach. The methodological approach has consisted of a literature review and document analysis, as well as, the application of semi-structured interviews with six social workers, two preceptors, a tutor, and three residents working at the Transplantation Care area. The research has included the themes relating to interdisciplinarity and the educational aspect of the social worker within the Health Multidisciplinary Residency. The interpretation of the data was based on Orlandi‟s perspective discourse analysis. The analyses have shown that the construction of the Resmulti / UFC and the insertion of the social worker in the program have happened in a vertical manner, resulting in estrangement from the preceptors, particularly because the services were in a resizing process. Regarding interdisciplinarity, the subjects conceptualize this dimension as the interconnection of knowledge in the context of the multidisciplinary team, strengthening the construction of the socialization of knowledge and shared actions. However, participants have highlighted the interdisciplinary actions are still sporadic, while recognizing the commitment of the social workers with respect to create moments in which interdisciplinarity has become effective, qualifying the training of residents and health care. Regarding the actions of the preceptors, the residents have pointed out some difficulties in the development of planned actions, identifying as an obstacle the various activities performed by the professionals. However, the residents have highlighted the contributions of the program to the professional maturity and the consolidation of the training in the field of interdisciplinary practices, seeking the deepening of actions based in technical-operative, theoretical-methodological and ethical-political dimensions. From the above mentioned, it is proposed that the residence corroborate the training of professionals politically engaged with the emancipatory project of society.